The Nearby Doctor Search Application Based on Android - Steven Wisnu Cahya Putra; Albertus Dwiyoga Widiantoro; Bernardinus Harnadi (Soegijapranata Catholic University, 2021)
This study aims to design the nearest doctor search application based on Android. The application is designed to find the nearest doctor and emergency room, show a list of emergency rooms and general doctor and specialists who open practice in Semarang area, and order queues online. The design of this application uses survey results to get data about application requirements. The application is designed based on the needs of the people who use the services of a private practice doctor and is expected to help the community in ordering queues to see a private practice doctor. The application was tested to 45 respondents ages 16-35 years who had tried the application 2-4 times. The test results state that application users will continue to be willing to use it if the application is easy to use and they have the device to run the application.